Analisis Permintaan Konsumen Terhadap Produk Pada Alexindo Aluminium Di Jalan Irian Palangka Raya - Siti Syuha; Rinto Alexandro; Tonich Uda; Dehen Erang; Susan Daniel; Hendrowanto Nibel (FKIP, Universitas Palangka Raya, 2022)
Demand is the amount of goods or services that consumers want and can afford at a predetermined price. Demand can also be said as a consumer's desire to get an item and service with the consumer's ability to buy. This ability is also closely related to the consumer's income. Prices for goods and services can also affect demand. The method used in this research is descriptive method, which is a method that aims to describe a problem clearly. The types of data used are primary data and secondary data. Data collection techniques consist of observation, interviews and documentation. The data analysis used is a qualitative data analysis technique which consists of 3 (three) stages of activities carried out sequentially, namely reducing data, presenting data, and drawing conclusions. The results of this study indicate that the consumer demand for Alexindo Aluminum Products on Jalan Irian Palangka Raya is that the most popular consumer demand is Aluminum Frames, Aluminum Cabinets and Rolling Doors by setting the right price, product quality, service and promotion strategies to increase consumer demand for products manufactured by Alexindo Aluminum on Jalan Irian Palangka Raya.